Flame-retardant composite material, preparation method and application thereof, flame-retardant diaphragm and lithium battery

By covalently grafting the phosphate flame retardant monomer on the surface of inorganic ceramic materials, a flame retardant composite material for lithium battery separators was prepared, which solved the problem of short-circuiting and flammable at high temperatures, achieving excellent flame retardant performance and thermal stability, while maintaining the electrochemical performance of the battery.

CN119751779APending Publication Date: 2025-04-04ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411919543.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing lithium battery separators are prone to shrink and melting at high temperatures, resulting in internal short circuits, and flammability increases the thermal runaway of the battery, causing fire and explosion.

Method used

Inorganic ceramic materials containing carbon-carbon double bonds and phosphate flame retardant monomers are used as the main preparation raw materials. Through the action of the initiator, the flame retardant is grafted on the surface of the inorganic ceramic material through covalent bonds to prepare a flame retardant composite material, and used to prepare a battery separator.

Benefits of technology

It improves the flame retardant performance and thermal stability of the battery separator, prevents the dissolution and release of flame retardant in the electrolyte, and automatically releases the flame retardant radical containing phosphorus to terminate the exothermic chain reaction, enhancing the safety of the battery without reducing the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207614520000091
    Figure BDA0005207614520000091
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and provides a flame-retardant composite material, a preparation method and application thereof, a flame-retardant diaphragm and a lithium battery. An inorganic ceramic material containing a carbon-carbon double bond, a phosphate flame retardant monomer containing a carbon-carbon double bond and an initiator are adopted as main preparation raw materials of the flame-retardant composite material, a flame retardant is grafted on the surface of the inorganic ceramic material in a covalent bond manner to obtain the flame-retardant composite material, and the flame-retardant composite material is further used for preparing a battery diaphragm. Not only is the flame retardant property of the battery diaphragm improved, but also the flame retardant can be prevented from being dissolved and released in electrolyte. Meanwhile, under the condition of heat abuse of the battery, the flame-retardant composite material can automatically release phosphorus-containing flame-retardant free radicals, remove hydrogen and hydroxyl radicals and terminate an exothermic chain reaction, so that the safety of the battery is improved, and the electrochemical performance of the battery is not reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and more specifically, to a flame retardant composite material and a preparation method and application thereof, a flame retardant diaphragm, and a lithium battery. Background Art

[0002] Lithium batteries are mainly composed of positive electrodes, negative electrodes, separators and electrolytes, among which the separator plays a vital role in the battery. The main function of the separator is to isolate the positive and negative electrodes and prevent the transfer of electrons, but allow the ions in the electrolyte to be transmitted between the positive and negative electrodes. Currently, the commercially available lithium flame-retardant separators are mainly polyolefin separators, such as polyethylene and polypropylene. Polyolefin separators have advantages such as good electrochemical stability and low manufacturing cost, but they also have disadvantages such as poor thermal stability and flammability, which leads to the polyolefin separator being prone to shrinkage and melting at high temperatures, thereby causing internal short circuits in lithium batteries; at the same time, the flammability of the polyolefin separator will aggravate the thermal runaway of the battery, causing the battery to catch fire and explode.

[0003] In order to solve the above problems, one of the commonly used methods is to improve the thermal stability of the diaphragm by coating inorganic ceramic materials such as aluminum oxide, silicon oxide, titanium oxide or oxide solid electrolyte on the surface of the polyolefin base film. However, when thermal runaway occurs, the flammable diaphragm and electrolyte will still aggravate the fire accident. The second commonly used method is to add flame retardants to commercial electrolytes to improve the safety of the battery, but flame retardants will also increase the viscosity of the electrolyte, resulting in a decrease in the ionic conductivity of the electrolyte, thereby reducing the rate performance of the battery, and most phosphate flame retardants have poor compatibility with electrodes, are easily decomposed in high-voltage positive electrode systems, and passivate graphite or lithium metal negative electrodes, thereby damaging the cycle life of the battery. Therefore, it is urgent to develop a flame retardant with excellent thermal stability and flame retardancy, which is further used to prepare battery diaphragms and assemble lithium batteries, which can improve the safety of lithium batteries without reducing the electrochemical performance of lithium batteries. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a flame-retardant composite material and its preparation method and application, a flame-retardant separator, and a lithium battery. The flame-retardant composite material provided by the present invention not only has excellent flame retardant properties, but also will not dissolve and release in the electrolyte, can be further used to prepare battery separators, and give the battery separators excellent flame retardant properties and thermal stability, thereby improving the safety of the battery without affecting the electrochemical properties of the battery.

[0005] A first aspect of the present invention provides a flame retardant composite material.

[0006] Specifically, a flame retardant composite material includes the following preparation raw materials:

[0007] Inorganic ceramic materials containing carbon-carbon double bonds,

[0008] Phosphate flame retardant monomers containing carbon-carbon double bonds,

[0009] Initiator.

[0010] The present invention uses an inorganic ceramic material containing a carbon-carbon double bond and a phosphate flame retardant monomer containing a carbon-carbon double bond as the main raw materials for preparation. Since both contain a carbon-carbon double bond, they can achieve chemical bonding under the action of an initiator, thereby grafting the flame retardant on the surface of the inorganic ceramic material by covalent bonding to obtain a flame retardant composite material, which is further used to prepare a battery separator, which not only improves the flame retardant performance and thermal stability of the battery separator, but also can prevent the flame retardant from dissolving and releasing in the electrolyte. At the same time, under the condition of thermal abuse of the battery, the flame retardant composite material will automatically release phosphorus-containing flame retardant free radicals, remove hydrogen and hydroxyl free radicals, terminate the exothermic chain reaction, and thus improve the safety of the battery.

[0011] Preferably, the mass of the phosphate flame retardant monomer containing carbon-carbon double bonds accounts for 1%-50% of the mass of the inorganic ceramic material containing carbon-carbon double bonds, and / or the mass of the initiator accounts for 0.5%-5% of the mass of the phosphate flame retardant monomer containing carbon-carbon double bonds.

[0012] Further preferably, the mass of the phosphate flame retardant monomer containing carbon-carbon double bonds accounts for 10%-40% of the mass of the inorganic ceramic material containing carbon-carbon double bonds, and / or the mass of the initiator accounts for 0.5%-4% of the mass of the phosphate flame retardant monomer containing carbon-carbon double bonds.

[0013] More preferably, the mass of the phosphate flame retardant monomer containing carbon-carbon double bonds accounts for 20%-30% of the mass of the inorganic ceramic material containing carbon-carbon double bonds, and / or the mass of the initiator accounts for 1%-3% of the mass of the phosphate flame retardant monomer containing carbon-carbon double bonds.

[0014] Preferably, the initiator is a thermal initiator.

[0015] More preferably, the initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide.

[0016] Preferably, the phosphate flame retardant monomer containing a carbon-carbon double bond is at least one of diethyl vinyl phosphate, diethyl allyl phosphate, diethyl allyl phosphate, and diethyl isopropenyl phosphate.

[0017] Preferably, the method for preparing the inorganic ceramic material containing carbon-carbon double bonds comprises the following steps:

[0018] A silane coupling agent containing a carbon-carbon double bond and an inorganic ceramic material containing a hydroxyl group are mixed, and the inorganic ceramic material containing a carbon-carbon double bond is prepared through a surface modification reaction.

[0019] The hydroxyl groups on the surface of the inorganic ceramic material undergo a condensation reaction with the silane coupling agent containing a carbon-carbon double bond to form a stable Si-O bond, so that the silane coupling agent containing a carbon-carbon double bond is grafted onto the surface of the inorganic ceramic material, and the modified inorganic ceramic material contains a carbon-carbon double bond so that the phosphate flame retardant can be covalently bonded later.

[0020] Preferably, before the mixing, the silane coupling agent containing carbon-carbon double bonds and the solvent are first mixed, and then the pH value is adjusted to 4-5 to obtain a precursor solution, and then the inorganic ceramic material containing hydroxyl groups is added and mixed.

[0021] Preferably, the weight of the silane coupling agent containing carbon-carbon double bonds accounts for 1%-30% of the weight of the inorganic ceramic material containing hydroxyl groups.

[0022] Further preferably, the weight of the silane coupling agent containing carbon-carbon double bonds accounts for 5%-25% of the weight of the inorganic ceramic material containing hydroxyl groups.

[0023] More preferably, the weight of the silane coupling agent containing carbon-carbon double bonds accounts for 10%-20% of the weight of the inorganic ceramic material containing hydroxyl groups.

[0024] Preferably, the silane coupling agent containing a carbon-carbon double bond is at least one of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane and 3-(isomethacryloyloxy)propyltrimethoxysilane.

[0025] Preferably, the solvent is water and / or ethanol.

[0026] Further preferably, the solvent is a mixed solution of ethanol and water in a volume ratio of (15-20):1.

[0027] Preferably, the reaction temperature is 60-80° C., and / or the reaction time is 5-15 h.

[0028] Preferably, the inorganic ceramic material containing hydroxyl groups is Al2O3, SiO2, TiO2, Li7La3Zr2O 12 、Li7La3Nb2O 12 , Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li1.4 Al 0.4 Ti 1.6 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 0.35 La 0.55 At least one of TiO3.

[0029] A second aspect of the present invention provides a method for preparing a flame retardant composite material.

[0030] A method for preparing a flame retardant composite material comprises the following steps:

[0031] The inorganic ceramic material containing carbon-carbon double bonds, the phosphate flame retardant monomer containing carbon-carbon double bonds and the initiator are mixed, and the flame retardant composite material is prepared through a thermal initiation reaction.

[0032] Preferably, the temperature of the thermal initiation reaction is 50-70° C., and / or the time of the thermal initiation reaction is 12-36 h.

[0033] Further preferably, the temperature of the thermal initiation reaction is 55-60° C., and / or the time of the thermal initiation reaction is 24-36 h.

[0034] Preferably, the mixing is to mix and disperse the inorganic ceramic material containing carbon-carbon double bonds, the phosphate flame retardant monomer containing carbon-carbon double bonds and the initiator in an organic solvent.

[0035] Preferably, the organic solvent is ethanol.

[0036] A third aspect of the present invention provides an application of a flame retardant composite material.

[0037] The invention discloses an application of a flame retardant composite material in the preparation of flame retardant electronic devices, flame retardant building materials, flame retardant furniture materials and flame retardant textiles.

[0038] A fourth aspect of the present invention provides a flame retardant membrane.

[0039] A flame retardant diaphragm comprises a base film and a flame retardant coating coated on the surface of the base film, wherein the components of the flame retardant coating include the flame retardant composite material, a binder and an organic solvent.

[0040] Preferably, the binder is at least one of polyvinylidene fluoride (PVDF), polymethyl methacrylate, sodium carboxymethyl cellulose, polystyrene butadiene copolymer, polyacrylic acid, polyethylene oxide, polypropylene carbonate, polyvinyl carbonate, polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, and polyvinylidene fluoride-hexafluoropropylene.

[0041] Preferably, the organic solvent is at least one of N-methylpyrrolidone, propylene carbonate, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, acetonitrile, tetrahydrofuran, acetone and methanol.

[0042] Preferably, the mass ratio of the flame retardant composite material to the binder is 97:3-70:30.

[0043] Further preferably, the mass ratio of the flame retardant composite material to the binder is 95:5-80:20.

[0044] Preferably, the base film is made of at least one of polyolefin, aramid, polyimide, polyvinylidene fluoride and polytetrafluoroethylene.

[0045] Preferably, the thickness of the flame retardant coating is 1-10 μm.

[0046] A fifth aspect of the present invention provides a method for preparing a flame retardant membrane.

[0047] A method for preparing a flame retardant diaphragm comprises the following steps:

[0048] The flame retardant composite material and a binder are first mixed to obtain slurry, and then the slurry is coated on the surface of a base film to obtain the flame retardant diaphragm.

[0049] A sixth aspect of the present invention provides a lithium battery.

[0050] A lithium battery comprises the flame-retardant diaphragm, a positive electrode, a negative electrode and an electrolyte.

[0051] Preferably, the positive electrode is stainless steel and / or lithium cobalt oxide.

[0052] Preferably, the negative electrode is lithium.

[0053] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0054] The present invention uses inorganic ceramic materials containing carbon-carbon double bonds, phosphate flame retardant monomers containing carbon-carbon double bonds, and initiators as the main raw materials for preparing flame-retardant composite materials. The inorganic ceramic materials and flame retardant monomers both contain carbon-carbon double bonds. Under the action of the initiator, chemical bonding is achieved, thereby grafting the flame retardant on the surface of the inorganic ceramic material by covalent bonds to obtain a flame-retardant composite material, which is further used to prepare a battery separator, which not only improves the flame retardant performance of the battery separator (such as the maximum heat release rate of the flame retardant separator can be as low as 256.1W / g, and the total heat release can be as low as 8.9kJ / g), but also can prevent the flame retardant from dissolving and releasing in the electrolyte. At the same time, under the condition of thermal abuse of the battery, the flame retardant composite material will automatically release phosphorus-containing flame retardant free radicals, remove hydrogen and hydroxyl free radicals, and terminate the exothermic chain reaction, thereby improving the safety of the battery, while not reducing the electrochemical performance of the battery (the ionic conductivity can reach 3.5×10 -3 S / cm, the electrochemical window can reach 4.6V and the battery capacity retention rate can be as high as 92%, with high ionic conductivity, wide electrochemical window and high battery capacity retention rate). DETAILED DESCRIPTION

[0055] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0056] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0057] Example 1

[0058] A flame retardant composite material, comprising the following preparation raw materials:

[0059] SiO2 containing vinyl group 5g,

[0060] 1g of diethyl vinyl phosphate,

[0061] Azobisisobutyronitrile initiator 0.0125g.

[0062] The method for preparing the flame retardant composite material comprises the following steps:

[0063] (1) 0.5 g of vinyl trimethoxysilane (silane coupling agent) was mixed evenly in 54 mL of ethanol solution and 3 mL of deionized water, and the pH of the mixed solution was controlled at 4-5 by adding acetic acid to obtain a precursor solution. Subsequently, 5 g of SiO2 (inorganic ceramic material) was added to the precursor solution and mixed evenly, and the mixture was stirred and heated at 70°C for 8 h. The powder was collected by centrifugation washing with ethanol and dried to finally obtain product A (SiO2 containing vinyl); compared with unmodified SiO2, the infrared spectrum of product A is 1652 cm -1 The appearance of new peaks is attributed to the infrared absorption peak of C=C bonds, indicating that the silane coupling agent is successfully modified on the surface of the inorganic ceramic material;

[0064] (2) 5 g of the product A in step 1, 1 g of vinyl diethyl phosphate and 0.0125 g of azobisisobutyronitrile were dispersed evenly in 30 mL of ethanol solution, and thermally initiated for 24 h at 60 ° C., and then centrifuged and washed with ethanol to remove unreacted vinyl diethyl phosphate, and finally dried to obtain product B (flame retardant composite material); relative to product A, the infrared absorption peak of C=C in the infrared spectrum of product B disappeared (1652 cm -1 ), indicating that the reaction between diethyl vinyl phosphate and product A has been completed, polymerization has occurred between the two, and the unreacted diethyl vinyl phosphate has been completely removed.

[0065] Example 2

[0066] A flame retardant composite material, which is different from Example 1 in that in step (2), the amount of product A is replaced by 20 g. The infrared absorption peak of C=C (1652 cm -1 ) compared with the infrared absorption peak at the corresponding position of product A, it still exists but weakens, indicating that the reaction between product A and diethyl vinyl phosphate is not complete at this ratio, and there is still unreacted C=C on the surface of product A; the content of flame retardant grafted on the surface of the flame-retardant composite material prepared in Example 2 is less than that in Example 1.

[0067] Example 3

[0068] A flame retardant composite material, which differs from Example 1 in that in step (2), vinyl diethyl phosphate is replaced by an equal weight of allyl diethyl phosphate. The infrared absorption peak of C=C in the infrared spectrum of the product flame retardant composite material disappears (1652cm -1 ), indicating that the reaction between allyl diethyl phosphate and product A has been completed, polymerization has occurred between the two, and the unreacted allyl diethyl phosphate has been completely removed.

[0069] Comparative Example 1

[0070] A flame retardant composite material, which differs from Example 1 in that, in step (1), an equal weight of 3-aminopropyltriethoxysilane (containing no vinyl group) is used instead of vinyltrimethoxysilane.

[0071] Comparative Example 2

[0072] A flame retardant composite material, which differs from Example 1 in that in step (2), an equal weight of trimethyl phosphate (free of vinyl group) is used instead of diethyl vinyl phosphate.

[0073] Application Example 1

[0074] A flame retardant diaphragm, the preparation method of which comprises: mixing 5 g of product B obtained in Example 1 and 0.26 g of PVDF in N-methylpyrrolidone to obtain a slurry, and then coating the slurry on both sides of a polyethylene diaphragm (base film), and obtaining a flame retardant diaphragm after drying, wherein the coating thickness is 2 μm.

[0075] Application Example 2

[0076] A flame retardant diaphragm is different from Application Example 1 in that the flame retardant composite material prepared in Example 2 of equal weight is used to replace the flame retardant composite material prepared in Example 1.

[0077] Application Example 3

[0078] A flame retardant diaphragm is different from Application Example 1 in that the flame retardant composite material prepared in Example 3 of equal weight is used to replace the flame retardant composite material prepared in Example 1.

[0079] Comparative application example 1

[0080] A flame retardant diaphragm, which differs from Application Example 1 in that an equal weight of Product A prepared in Example 1 is used to replace Product B prepared in Example 1.

[0081] Comparative Application Example 2

[0082] A flame retardant diaphragm, which differs from Application Example 1 in that an equal weight of the flame retardant composite material prepared in Comparative Example 1 is used to replace the product B prepared in Example 1.

[0083] Comparative Application Example 3

[0084] A flame retardant diaphragm, which differs from Application Example 1 in that an equal weight of the flame retardant composite material prepared in Comparative Example 2 is used to replace the product B prepared in Example 1.

[0085] Comparative Application Example 4

[0086] A flame retardant diaphragm, which differs from Application Example 1 in that an equal weight of SiO2 is used to replace the product B prepared in Example 1.

[0087] Product effect testing

[0088] 1. Flame retardant properties

[0089] (1) Test method: A microcalorimeter is used to measure the flame retardant properties of the diaphragm, with the maximum test temperature being 700°C and the heating rate being 1°C / s. Reference test standard: ASTM D7309-2007. The test results of the maximum heat release rate and total heat release of the flame retardant diaphragms prepared in the above-mentioned application examples and comparative application examples are shown in the following table (generally speaking, excellent flame retardant properties require relatively low maximum heat release rate and total heat release).

[0090] Table 1 Maximum heat release rate and total heat release of flame retardant diaphragms prepared in various application examples and comparative application examples

[0091] Flame retardant diaphragm Maximum heat release rate (W / g) Total heat release (kJ / g) Application Example 1 256.1 8.9 Application Example 2 388.5 15.4 Application Example 3 345.3 10.8 Comparative application example 1 812.4 47.3 Comparative Application Example 2 613.8 38.5 Comparative Application Example 3 788.1 45.9 Comparative Application Example 4 1073.6 61.4

[0092] It can be seen from Table 1 that the maximum heat release rate and total heat release of application examples 1-3 are lower than those of comparative application examples 1-4, among which the maximum heat release rate of the flame-retardant membrane prepared in application example 1 is as low as 256.1W / g, and the total heat release is as low as 8.9kJ / g, which are lower than those of application examples 2-3 and comparative application examples 1-4. Application example 1 performs best, indicating that the coated membrane prepared in application example 1 has excellent flame retardant properties and thermal stability. This is mainly attributed to the fact that the phosphate flame retardant monomer is covalently grafted on the surface of the inorganic ceramic material SiO2 by chemical modification method in Example 1 of the present invention, and phosphorus-containing flame retardant free radicals are released during the heating process, cutting off the exothermic chain reaction, thereby reducing the heat release rate and total heat release, and improving the flame retardant properties. The maximum heat release rate and total heat release of the flame retardant membrane prepared in application example 1 are lower than those in application example 2, which is attributed to the fact that the flame retardant composite material prepared in application example 1 contains more flame retardant than the flame retardant composite material prepared in application example 2.

[0093] Comparative Application Example 1 and Comparative Application Example 4 are both not modified by flame retardants and do not contain flame retardants, resulting in poor flame retardant properties of the diaphragm. In the process of preparing the composite material, the silane coupling agent used in Comparative Application Example 2 does not contain a carbon-carbon double bond, resulting in the prepared composite material being only grafted with the silane coupling agent on the surface of the inorganic material, and the phosphate flame retardant monomer cannot be covalently grafted on the silane coupling agent through a chemical bond, but only the phosphate flame retardant monomer itself is polymerized, and the polymerized phosphate monomer is easily removed during the centrifugal washing process, and the prepared composite material does not contain a flame retardant. The phosphate flame retardant monomer used in Comparative Application Example 3 does not contain a carbon-carbon double bond, and is also only grafted with a silane coupling agent on the surface of the inorganic material, and the phosphate flame retardant monomer fails to undergo a polymerization reaction and still exists in the form of a monomer. The phosphate flame retardant monomer can be directly and completely removed during the centrifugal washing process, and the prepared composite material does not contain a flame retardant. Therefore, both Comparative Application Example 2 and Comparative Application Example 3 will result in the inability of the phosphate flame retardant monomer to be covalently grafted onto the surface of the inorganic material through chemical bonds, that is, the prepared composite material does not contain a flame retardant component, resulting in poor flame retardant properties.

[0094] 2. Electrochemical performance

[0095] (1) Test method

[0096] ① Test of ionic conductivity: Cut the flame-retardant diaphragm in Application Example 1 into small discs with a diameter of 16 mm, and assemble them into a CR2032 symmetrical battery using two stainless steel discs with a diameter of 15.8 mm. The electrolyte is 1 mol / L LiPF6 in EC (ethylene carbonate) / EMC (ethyl methyl carbonate) (EC:EMC volume ratio = 3:7), and the amount of electrolyte is 50 μL. The assembled symmetrical battery was subjected to electrochemical impedance spectroscopy test on an electrochemical workstation, with a test frequency range of 1 MHz to 0.1 Hz and an amplitude of 10 mV. The calculation formula for ionic conductivity is: σ = L / (R×S), where σ is the ionic conductivity of the diaphragm (S / cm), L is the thickness of the diaphragm (cm), R is the impedance of the symmetrical battery (Ω), and S is the area of ​​the diaphragm (cm 2 ).

[0097] ②Electrochemical window test: Cut the flame-retardant diaphragm in Application Example 1 into small discs with a diameter of 16 mm, use a lithium sheet as the negative electrode and a stainless steel disc as the positive electrode to assemble a CR2032 battery, where the electrolyte is 1 mol / L LiPF6 EC / EMC (EC:EMC volume ratio = 3:7), and the amount of electrolyte is 50 mL. Use an electrochemical workstation to perform linear sweep voltammetry on the battery to test the electrochemical window of the diaphragm, with a scan rate of 1 mV / s.

[0098] ③ Battery cycle performance test: With lithium metal as the negative electrode and lithium cobalt oxide as the positive electrode, the flame-retardant diaphragm in Application Example 1 was used to assemble a CR2032 battery, wherein the electrolyte was 1 mol / L LiPF6 EC / EMC (EC:EMC volume ratio = 3:7), and the electrolyte dosage was 50 μL. At a current density of 1C, 100 cycle performance tests were performed, and the operating voltage range was 3.0-4.5V.

[0099] In addition, one of the commonly used methods to improve battery safety is to add flame retardants to the electrolyte, so this is used as a control example, specifically: 10wt% of vinyl diethyl phosphate or the flame retardant composite material B prepared in Example 1 is added to 1mol / L LiPF6 EC / EMC electrolyte, where the EC:EMC volume ratio is 3:7, to obtain an electrolyte containing flame retardants; then the electrolyte containing flame retardants is subjected to the electrochemical performance tests of the above ①-③. Compare the ionic conductivity, electrochemical window and battery cycle performance of the three methods of directly introducing the flame retardant (vinyl diethyl phosphate) and the flame retardant composite material B prepared in Example 1 into the electrolyte and fixing the flame retardant (vinyl diethyl phosphate) on the diaphragm.

[0100] The above electrochemical performance test results are shown in the following table.

[0101] Table 2 Electrochemical performance test results of different lithium batteries

[0102]

[0103] It can be seen from the above table that compared with methods 2 and 3, method 1 exhibits higher ionic conductivity, wider electrochemical window and higher battery capacity retention rate, indicating that the flame retardant diaphragm prepared in application example 1 of the present invention and the lithium battery assembled therefrom, while improving the flame retardant properties, do not affect the electrochemical properties of the battery, and maintain the good electrochemical properties of the lithium battery.

[0104] On the one hand, the reduction in ionic conductivity of method 3 is mainly attributed to the direct addition of vinyl diethyl phosphate flame retardant into the electrolyte. Although it improves the flame retardant performance, it also leads to an increase in the viscosity of the electrolyte, thereby reducing the ionic conductivity; and most phosphate flame retardants have poor compatibility with electrodes, are easily decomposed in high-voltage positive electrode systems, and passivate graphite or lithium metal negative electrodes, thereby damaging the cycle life of the battery. The reduction in ionic conductivity of method 2 is mainly attributed to the direct addition of the flame retardant composite material into the electrolyte, which increases the viscosity of the electrolyte; but compared with method 3, method 2 uses the flame retardant composite material prepared in Example 1, and the flame retardant is chemically covalently grafted on the surface of the inorganic material, which inhibits the release of the flame retardant in the electrolyte, thereby improving the electrochemical window of the electrolyte and improving the passivation of the flame retardant to the negative electrode to a certain extent relative to method 3. In method 1, the flame-retardant diaphragm of application example 1 is used. The flame-retardant diaphragm grafts vinyl diethyl phosphate onto the surface of the inorganic ceramic material through chemical covalent bonding to prevent the dissolution and release of the flame retardant in the electrolyte, thereby not affecting the viscosity of the electrolyte. Therefore, it has higher ionic conductivity, electrochemical window and battery capacity retention rate.

[0105] On the other hand, the free flame retardant in method 3 is easy to decompose and react under high pressure, resulting in a narrow electrochemical window. However, the flame retardant in method 1 is chemically grafted on the surface of the inorganic ceramic material, and there are no free flame retardant molecules, so it presents an electrochemical window as high as 4.6V, and can ensure the stable operation of lithium batteries with high-voltage positive electrode systems. Therefore, in the cycle stability test of lithium batteries, the capacity retention rate of batteries assembled in method 1 is much higher than that of method 3.

Claims

1. A flame retardant composite material, characterized in that: The preparation includes the following raw materials: Inorganic ceramic materials containing carbon-carbon double bonds, Phosphate flame retardant monomer and initiator containing carbon-carbon double bonds.

2. The flame retardant composite material according to claim 1, characterized in that: The mass of the phosphate flame retardant monomer containing carbon-carbon double bonds accounts for 1%-50% of the mass of the inorganic ceramic material containing carbon-carbon double bonds, and / or the mass of the initiator accounts for 0.5%-5% of the mass of the phosphate flame retardant monomer containing carbon-carbon double bonds.

3. The flame retardant composite material according to claim 1, characterized in that: The phosphate flame retardant monomer containing a carbon-carbon double bond is at least one of diethyl vinyl phosphate, diethyl allyl phosphate, diethyl allyl phosphate, and diethyl isopropenyl phosphate.

4. The flame retardant composite material according to claim 1, characterized in that: The method for preparing the inorganic ceramic material containing carbon-carbon double bonds comprises the following steps: A silane coupling agent containing a carbon-carbon double bond and an inorganic ceramic material containing a hydroxyl group are mixed, and the inorganic ceramic material containing a carbon-carbon double bond is prepared through a surface modification reaction.

5. The flame retardant composite material according to claim 4, characterized in that: The weight of the silane coupling agent containing carbon-carbon double bonds accounts for 1%-30% of the weight of the inorganic ceramic material containing hydroxyl groups.

6. The method for preparing the flame retardant composite material according to any one of claims 1 to 5, characterized in that: The steps include: The inorganic ceramic material containing carbon-carbon double bonds, the phosphate flame retardant monomer containing carbon-carbon double bonds and the initiator are mixed, and the flame retardant composite material is prepared through a thermal initiation reaction.

7. Use of the flame-retardant composite material according to any one of claims 1 to 5 in the preparation of flame-retardant electronic devices, flame-retardant building materials, flame-retardant furniture materials, and flame-retardant textiles.

8. A flame retardant diaphragm, characterized in that: The invention comprises a base film and a flame retardant coating coated on the surface of the base film, wherein the components of the flame retardant coating include the flame retardant composite material according to any one of claims 1 to 5, a binder and an organic solvent.

9. The method for preparing the flame retardant diaphragm according to claim 8, characterized in that: The steps include: Firstly, the flame-retardant composite material according to any one of claims 1 to 5 is mixed with a binder to obtain a slurry, and then the slurry is coated on the surface of a base film to obtain the flame-retardant diaphragm.

10. A lithium battery, characterized in that: It comprises the flame-retardant diaphragm as claimed in claim 8, a positive electrode, a negative electrode and an electrolyte.